2019
DOI: 10.1111/bjd.18086
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal autophagy and beclin 1 regulator 1 and loricrin: a paradigm shift in the prognostication and stratification of the American Joint Committee on Cancer stage I melanomas

Abstract: Summary Background The updated American Joint Committee on Cancer (AJCC) staging criteria for melanoma remain unable to identify high‐risk stage I tumour subsets. Objectives To determine the utility of epidermal autophagy and beclin 1 regulator 1 (AMBRA1)/loricrin (AMLo) expression as a prognostic biomarker for AJCC stage I cutaneous melanoma. Methods Peritumoral AMBRA1 expression was evaluated in a retrospective discovery cohort of 76 AJCC stage I melanomas. AMLo expression was correlated with clinical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 18 publications
(25 reference statements)
5
34
0
Order By: Relevance
“…There is interest in developing biomarkers that can accurately identify high‐risk early stage disease from low‐risk early stage disease, though many of these require validation in larger cohorts before they are ready for clinical implementation. Many of the biomarkers published to date have relied on cohorts with relatively short‐term outcome data, 16–18 while one study relies on 12‐year outcome data 19 . When validating biomarkers to risk stratify early stage disease, our analyses indicate that it is important to consider follow‐up to 20 years to capture most of the fatalities.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There is interest in developing biomarkers that can accurately identify high‐risk early stage disease from low‐risk early stage disease, though many of these require validation in larger cohorts before they are ready for clinical implementation. Many of the biomarkers published to date have relied on cohorts with relatively short‐term outcome data, 16–18 while one study relies on 12‐year outcome data 19 . When validating biomarkers to risk stratify early stage disease, our analyses indicate that it is important to consider follow‐up to 20 years to capture most of the fatalities.…”
Section: Discussionmentioning
confidence: 92%
“…Many of the biomarkers published to date have relied on cohorts with relatively short-term outcome data, [16][17][18] while one study relies on 12-year outcome data. 19 When validating biomarkers to risk stratify early stage disease, our analyses indicate that it is important to consider follow-up to 20 years to capture most of the fatalities.…”
Section: Discussionmentioning
confidence: 97%
“…The optimum cut-point was identified at an H-score of 140 with a sensitivity of 55% (95% CI 39.83% -69.29%), specificity of 62.79% (95% CI 47.86% -75.62%) and a likelihood ratio of 1.48. Binary scores of 0 for low-risk (H-score <140) and 1 for high-risk (H-score > or = to 140) were applied for further Kaplan-Meier survival curve analysis 15 Other variables assessed included age, sex, HPV status and AMBRA1 tumor positivity.…”
Section: Discussionmentioning
confidence: 99%
“…Ellis et al (30) have observed increased expression of autophagy receptor p62 in early AJCC stage melanomas, which was subsequently decreased in advanced metastatic tumors. Decreased or even complete loss of AMBRA1 expression has been observed in the epidermis overlying AJCC stage I melanomas, but not in benign nevi (31) suggesting the prognostic potential of this marker. Another study has shown that loss of Atg7 prevents melanoma development in BrafV600E mutant mice with allelic loss of Pten gene (32).…”
Section: Discussionmentioning
confidence: 96%